The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00339-016-9964-3
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of laser-induced breakdown spectroscopy in screening potential additives to mitigate fouling deposits

Abstract: Alkali vapors present in the flue gas generated during coal-based combustion form fouling deposits as they condense. An additive added to coal can trap alkali elements in ash, therefore suppress the growth rate of fouling deposits, and increase thermal efficiency of a coalfired thermal power plant. Laser-induced breakdown spectroscopy (LIBS) technique is proposed and demonstrated to screen potential additives to trap alkali elements in ash. Five additives-namely, kaolinite, alumina, silica, magnesia, and pumic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Various studies have reported the characterization of coal using LIBS to determine C content, ash content, calorific value, volatile matter content, etc. 59 Most of the reported studies involve sample preparation where the coal samples were ball milled and compacted into pellets to achieve an even surface and homogeneous composition. 10,11 But in real-time, coal composition is not uniform throughout the sample, and coal pieces are irregularly shaped, which is the major challenge in LIBS analysis of coal.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported the characterization of coal using LIBS to determine C content, ash content, calorific value, volatile matter content, etc. 59 Most of the reported studies involve sample preparation where the coal samples were ball milled and compacted into pellets to achieve an even surface and homogeneous composition. 10,11 But in real-time, coal composition is not uniform throughout the sample, and coal pieces are irregularly shaped, which is the major challenge in LIBS analysis of coal.…”
Section: Introductionmentioning
confidence: 99%